Uniportal Thoracoscopic Debridement for Children With Refractory Pleural Empyema: Case Series of 21 Patients - Huang, Jin-Xi; Chen, Qiang; Hong, Song-Ming; Hong, Jun-Jie; Cao, Hua (Frontiers in Pediatrics, 2021)
Purpose: The effectiveness of video-assisted thoracic surgery (VATS), even of uniportal-VATS (U-VATS), in the treatment of pleural empyema has recently been proven. However, few works evaluated its safety and feasibility for children. We review our experience with U-VATS in the treatment of pleural empyema for children under 11 years old. Methods: From January 2019 to December 2020, we enrolled 21 consecutive children with stage Ⅱ and stage Ⅲ pleural empyema in our institution. A 1.0 cm utility port was created in the 5th intercostal space at the anterior axillary line. A rigid 30° 5mm optic thoracoscope was used for vision, and two or three instruments were used through the port. Surgery is based on three therapeutic columns: removal of pleural fluid, debridement and decortication. A chest tube is inserted through the same skin incision. Perioperative data and outcomes were summarized. Results: The procedures were successful and satisfactory debridement of the pleural cavity were achieved in all cases. Mean age was 4.1 years (range, 6 months to 11 years). Mean operating time was 65.7±23.2 minutes. No intraoperative conversion or major complications were identified among the patients. Mean hospital stay was 5.0 ± 0.6 days. At a follow-up of more than 4 months, all patients recovered well without recurrence. Conclusion: According to our experience, U-VATS debridement is feasible for the surgical management of stages Ⅱ and Ⅲ empyema in the pediatric population. Indeed, U-VATS permits an easier performance and complete debridement and decortication, with a very low risk for conversion.